Immigrants and Refugees: From Social Disaffection to Perceived Threat - Vala, Jorge (2020)
Immigrants and refugees are today represented as a threat by a significant number of Europeans and constitute a topic that divides Governments and is at the centre of the agenda of new European extreme right-wing. This chapter presents a new approach and innovative hypotheses about the factors underlying the representation of immigrants and refugees as a threat, and their role in legitimizing discrimination, social inequalities and the development of anti-immigrant and anti-refugee public policies. Our approach is based on the hypothesis that immigrants and refugees are perceived as a threat to individual and collective life projects, particularly by those experiencing a sense of social disaffection (i.e., a generalized feeling that conjointly expresses dissatisfaction with life, perception of lack of control over life and distrust of the social system’s nuclear institutions). Using new data from the European Social Survey, we propose an analytical model specifying the correlates of threat perceptions and the mediating role of threat on the relationship between social disaffection and opposition to immigration and refugees in Europe. Results have shown that the sense of threat is related to right-wing political positioning, exclusive national identity, anti-universalistic values and, more importantly, with the sense of social disaffection. Significantly, threat perceptions play a legitimating role in the relationship between social disaffection and opposition to immigration and to hosting refugees. We further discuss the theoretical and socio-political implications of our approach to the study of threat in the context of contemporary social dynamics.